Distinct Lotus japonicus Transcriptomic Responses to a Spectrum of Bacteria Ranging From Symbiotic to Pathogenic - Kelly, Simon; Mun, Terry; Stougaard, Jens; Ben, Cécile; Andersen, Stig U. (Frontiers in Plant Science, 2018)
Lotus japonicus is a well-studied nodulating legume and a model organism for the investigation of plant-microbe interactions. The majority of legume transcriptome studies have focused on interactions with compatible symbionts, whereas responses to non-adapted rhizobia and pathogenic bacteria have not been well-characterized. In this study, we first characterized the transcriptomic response of L. japonicus to its compatible symbiont, Mesorhizobium loti R7A, through RNA-seq analysis of various plant tissues. Early symbiotic signaling was largely Nod factor-dependent and enhanced within root hairs, and we observed large-scale transcriptional reprogramming in nodule primordia and mature nitrogen-fixing nodules. We then characterized root transcriptional responses to a spectrum of L. japonicus interacting bacteria ranging from semi-compatible symbionts to pathogens. M. loti R7A and the semi-compatible strain Sinorhizobium fredii HH103 showed remarkably similar responses, allowing us to identify a small number of genes potentially involved in differentiating between fully and semi-compatible symbionts. The incompatible symbiont Bradyrhizobium elkanii USDA61 induced a more attenuated response, but the weakest response was observed for the foliar pathogen Pseudomonas syringae pv. tomato DC3000, where the affected genes also responded to other tested bacteria, pointing to a small set of common bacterial response genes. In contrast, the root pathogen Ralstonia solanacearum JS763 induced a pronounced and distinct transcriptomic pathogen response, which we compared to the results of the other treatments. This comparative analysis did not support the concept that an early defense-like response is generally evoked by compatible rhizobia during establishment of symbiosis.